Endothelial cell vasodilator dysfunction mediates progressive pregnancy-induced hypertension in endothelial cell tetrahydrobiopterin deficient mice. - Chuaiphichai, S; Dickinson, Y; Whiteman, CAR; Au-Yeung, D; McNeill, E; Channon, KM; Douglas, G (Elsevier, 2023)
Background and purpose: Pregnancy-associated vascular remodelling is essential for both maternal and fetal health. We have previously shown that maternal endothelial cell tetrahydrobiopterin (BH4) deficiency causes poor pregnancy outcomes. Here, we investigated the role and mechanisms of endothelial cell-mediated vasorelaxation function in these outcomes. Experimental approach: The vascular reactivity of mouse aortas and uterine arteries from non-pregnant and pregnant endothelial cell-specific BH4 deficient mice (Gch1fl/flTie2cre mice) was assessed by wire myography. Systolic blood pressure was assessed by tail cuff plethysmography. Key results: In late pregnancy, systolic blood pressure was significantly higher (∼24 mmHg) in Gch1fl/flTie2cre mice compared with wild-type littermates. This was accompanied by enhanced vasoconstriction and reduced endothelial-dependent vasodilation in both aorta and uterine arteries from pregnant Gch1fl/flTie2cre mice. In uterine arteries loss of eNOS-derived vasodilators was partially compensated by upregulation of intermediate and large-conductance Ca2+-activated K+ channels. In rescue experiments, oral BH4 supplementation alone did not rescue vascular dysfunction and pregnancy-induced hypertension in Gch1fl/flTie2cre mice. However, combination with the fully reduced folate, 5-methyltetrahydrofolate (5-MTHF), restored endothelial cell vasodilator function and blood pressure. Conclusions and implications: We identify a critical requirement for maternal endothelial cell Gch1/BH4 biosynthesis in endothelial cell vasodilator function in pregnancy. Targeting vascular Gch1 and BH4 biosynthesis with reduced folates may provide a novel therapeutic target for the prevention and treatment of pregnancy-related hypertension.